Pengaruh Minyak Atsiri Bunga Kenanga (Cananga Odorata) dalam Formulasi Body Lotion Berbasis Minyak VCO - Ahmad, Fachraniah; Elwina, Elwina; Amalia, Zuhra; Habibah, Ummi (Politeknik Negeri Lhokseumawe, 2025)
This study aims to examine the effect of the addition of kenanga essential oil on the manufacture of body lotion as an antibacterial with VCO oil as the basic ingredient. VCO oil is very good for the skin and to add to the advantages of the body lotion, kenanga oil is added as an anti-bacterial and anti-oxidant ingredient for the skin. The body lotion formula used is the formulation of ingredients using Virgin Coconut Oil (VCO), olive oil, rose water, and beeswax. This research was conducted by mixing the three ingredients, namely olive oil, beeswax and VCO. Then heat it at 50°C, then homogenized. Next, rose water and ylang ylang oil were added to the mixture. All ingredients were then stirred until evenly distributed, ensuring the homogeneity of the resulting lotion. Then the product was analyzed including antioxidant test, bacterial test, and organoleptic test. Organoleptic test was conducted to determine the characteristics of the physical properties of the body lotion produced including aroma and moisture. body lotion is a very strong antioxidant (IC50 value 50). For the 10 mL VCO variation, the 8 mL essential oil variation shows the best IC50 value of 16.71 µg/mL and the 20 mL VCO variation, at 8 mL essential oil shows the best IC50 value of 14.39 µg/mL. The results of the analysis after the use of body lotion with a sample of 8 mL essential oil and 20 mL VCO there are fewer colonies with a value of 3 APM colonies / gram, the sample still meets the requirements of microbial contamination according to SNI because it does not exceed 3 APM / gram and in accordance with SNI body lotion 2016.